Analysis of General Chemistry Textbooks Based on Multiple Representations of the Cell Potential Concept - Annisa Shafira Muntaha; Wiji Wiji; Tuszie Widhiyanti; Sri Mulyani (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2025)
Textbooks function as core learning resources in chemistry, particularly for explaining abstract ideas through visual representations. This study examines how the concept of electrochemical potential cells is represented in five college level general chemistry textbooks using five analytic criteria covering representation type, explicitness, connectedness, information sufficiency, and conceptual relatedness. The sample comprises widely adopted texts that span foundational topics to ensure relevance across common curricula. The analysis identified a distinct pattern within each category. Category C1 was dominated by symbolic representations at 74.7 percent. Category C2 showed predominantly explicit presentations at 79.3 percent. Category C3 reflected fully related and connected representations. Category C4 demonstrated complete presence of appropriate information at 100 percent. Category C5 included three levels of conceptual relatedness with quite related at 74.2 percent, not quite related at 19.4 percent, and not related at 6.5 percent. The findings outline the current quality of visual representations of potential cells in higher education materials and indicate areas where integration across macroscopic, submicroscopic, and symbolic levels could be strengthened. Educators, textbook authors, and curriculum developers can apply these insights to design materials that support deeper conceptual understanding and more coherent transitions between representations.